2016
DOI: 10.1177/0266242616630356
|View full text |Cite
|
Sign up to set email alerts
|

Student entrepreneurial optimism and overconfidence across cultures

Abstract: In this article, we examine whether university students are optimistic and/or overconfident about entrepreneurship, and the impact this has on their entrepreneurial intentions. We do so in three different nations corresponding to three different cultural clusters. Findings suggest that, students are optimistic—with American students being the most optimistic in comparison to their Spanish and Indian peers—but not overconfident. In addition, we find family support to moderate the relationship between entreprene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 100 publications
(122 reference statements)
2
32
0
4
Order By: Relevance
“…Optimism is a longterm and stable personality trait that is difficult to change, while overconfidence is a reaction to specific events. However, prior studies used optimism and overconfidence interchangeably (Cassar, 2010) and conflated (Trevelyan, 2008;Giacomin, Janssen, & Shinnar, 2016), and fail to discuss their differences. Parker (2009) indicated that conflating optimism and overconfidence should not be encouraged in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Optimism is a longterm and stable personality trait that is difficult to change, while overconfidence is a reaction to specific events. However, prior studies used optimism and overconfidence interchangeably (Cassar, 2010) and conflated (Trevelyan, 2008;Giacomin, Janssen, & Shinnar, 2016), and fail to discuss their differences. Parker (2009) indicated that conflating optimism and overconfidence should not be encouraged in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Национальная культура способна сформи-ровать склонность индивида к предприни-мательству через развитие соответствую-щих психологических черт [Shinnar, Giacomin, Janssen, 2012;De Clercq, Lim, Oh, 2014;Stephan, Pathak, 2016] Подход социальной леги-тимности, или «морального одобрения», предпринима-тельского поведения Легитимация предпринимательской деятельности на уровне общественных норм и установок ведет к увеличению доли предпринимателей среди носителей культуры Giacomin, Janssen, Shinnar, 2016;Laskovaia, Shirokova, Morris, 2017] Подход «неудовлетворенно-сти» индивида статус-кво Различия в ценностях потенциального предпринимателя и общества в целом являются причиной неудовлетворенности существующими возможностями развития карьеры, что в конечном итоге ведет к выбору предпринимательского пути [Shneor, Camgöz, Karapinar, 2013;Bachmann, Engelen, Schwens, 2016] В каждом из отобранных журналов был проведен поиск статей по терминам "national culture" (culture) и "entrepreneurship". Поиск проводился по названию, аннотации и ключевым словам статей.…”
Section: используемый метод анализа литературыunclassified
“…Третье направление исследований связи национальной культуры и предпринима-тельства рассматривает роль культуры в формировании индивидуальной предпри-нимательской активности De Clercq, Lim, Oh, 2013;Stephan, Pathak, 2016;Shirokova, Tsukanova, Morris, 2018] и предпринимательских намерений [Liñán, Chen, 2009;Shinnar, Giacomin, Janssen, 2012;Shneor, Camgöz, Karapinar, 2013;Giacomin, Janssen, Shinnar, 2016]. Особое внимание уделяется также изуче-нию личностных характеристик, присущих предпринимателю [McGrath, MacMillan, Scheinberg, 1992;Mueller, Thomas, 2001;Thomas, Mueller, 2000;Stewart et al, 2003]; предпринимательского познания [Mitchell et al, 2000;Mitchell et al, 2002]; отношения к предпринимательству [Drakopoulou Dodd, Jack, Anderson, 2013] и же-лательности и возможности предприни-мательского поведения [Minola, Criaco, Obschonka, 2016], поскольку они способны оказать воздействие на поведение индиви-да и его намерения открыть собственный бизнес.…”
Section: направления исследований связи национальной культуры и предпunclassified
See 2 more Smart Citations